Linguistic manifestations in the elderly: the role of speech and language intervention in healthy and pathological aging - González Martín, Enrique; Mendizábal de la Cruz, Nieves; Jimeno Bulnes, Natalia; Sánchez Gil, Carolina (Revista de Investigación en Logopedia, 2019)
It has recently become particularly important to gain more knowledge about the linguistic and communicative abilities of the population who are over 65 years of age. The biological, psychological and social changes that this group of people suffers should be addressed taking into account the interaction between the cognitive and linguistic domains. With this in mind, the objective of this paper is to provide a literature review of linguistic manifestations, covering both common and pathological aging. Results show that the most outstanding features are mainly related to the difficulty of accessing the lexical label of words, the slowness of speech and the difficulty in maintaining the topic of the speech. Specialized-speech and language-therapy intervention (logopedic) is crucial to control and address these linguistic symptoms. It is for this reason that the need for speech and language-therapy intervention is highlighted. This intervention should be done by focusing on the specific characteristics and needs of aged people, taking as a point of departure the metalinguistic function of language.